1986
DOI: 10.2466/pms.1986.63.1.87
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Heart Rate during Feedback Control of Respiration

Abstract: Subjects received one of eight treatments: practice at increasing heart rate with heart-rate feedback, practice at decreasing heart rate with heart-rate feedback, practice at increasing heart rate without heart-rate feedback, practice at decreasing heart rate without heart-rate feedback, practice at increasing respiration rate with respiratory feedback, practice at decreasing respiration rate with respiratory feedback, practice at increasing respiration rate with respiratory instructions only, practice at decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
1996
1996

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…3 Changes in heart rate and RSA also are dissociated in response to chemical anesthesia (Donchin, Feld, & Porges, 1985). Although several biofeedback studies found that slow breathing facilitates voluntary decrease in heart rate (de Pascalis, Anello, & Venturini, 1986;Holmes et al, 1979Holmes et al, , 1980, others have found that the effects on this measure are very small (Allen & Crowell, 1990;Epstein & Webster, 1975;Grossman & Kollai, 1993;McCaul, Solomon, & Holmes, 1979). These studies all point to a partial dissociation between mechanisms involving nonsympathetic control of RSA and average heart rate.…”
Section: The Effects Of Paced Breathing On Respiratory Sinus Arrhythmmentioning
confidence: 99%
“…3 Changes in heart rate and RSA also are dissociated in response to chemical anesthesia (Donchin, Feld, & Porges, 1985). Although several biofeedback studies found that slow breathing facilitates voluntary decrease in heart rate (de Pascalis, Anello, & Venturini, 1986;Holmes et al, 1979Holmes et al, , 1980, others have found that the effects on this measure are very small (Allen & Crowell, 1990;Epstein & Webster, 1975;Grossman & Kollai, 1993;McCaul, Solomon, & Holmes, 1979). These studies all point to a partial dissociation between mechanisms involving nonsympathetic control of RSA and average heart rate.…”
Section: The Effects Of Paced Breathing On Respiratory Sinus Arrhythmmentioning
confidence: 99%